Citizens’ Rights And The Enforcement Of Conservation Laws: A Plea For A Comparative And Multi-Faceted Approach - Abdullah, Sulaiman (Journal of Malaysian and Comparative Law, 2019)
Every processional is aware of the sense of awe with which the average citizen approaches the mysteries of any particular profession.